Upgrading In Vitro Digestion Protocols with Absorption Models - Otilia Antal; István Dalmadi; Krisztina Takács (Applied Sciences, 2024)
Intestinal digestion and absorption are complex processes; thus, it is a challenge to imitate them realistically. There are numerous approaches available, with different disadvantages and advantages. The simplest methods to mimic absorption are the non-cell-based transport models but these lack important characteristics of enterocytes of the intestine. Therefore, the most often used method is to measure absorption through viable mammalian cells (most commonly Caco-2 cells, cultured on membrane insert plates), which not only assures the incorporation of brush border enzymes (responsible for the final digestion of peptides and disaccharides), it also simulates the absorption process. This means that influx/efflux transporter-facilitated transport, carrier-mediated transport, endocytosis, and transcytosis is also imitated besides passive diffusion. Still, these also lack the complexity of intestinal epithelium. Organoids or ex vivo models are a better approach if we want to attain precision but the highest accuracy can be achieved with microfluidic systems (gut-on-a-chip models). We propose that more research is necessary, and food absorption should also be studied on gut-on-a-chips, especially with fragmented organoids. Our review supports the choices of a proper intestinal epithelium model, which may have a key role in functional food development, nutrition studies, and toxicity assessment.